2007
DOI: 10.1016/j.devcel.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

MIWI2 Is Essential for Spermatogenesis and Repression of Transposons in the Mouse Male Germline

Abstract: Small RNAs associate with Argonaute proteins and serve as sequence-specific guides for regulation of mRNA stability, productive translation, chromatin organization, and genome structure. In animals, the Argonaute superfamily segregates into two clades. The Argonaute clade acts in RNAi and in microRNA-mediated gene regulation in partnership with 21-22 nt RNAs. The Piwi clade, and their 26-30 nt piRNA partners, have yet to be assigned definitive functions. In mice, two Piwi-family members have been demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
1,019
2
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,038 publications
(1,058 citation statements)
references
References 55 publications
25
1,019
2
12
Order By: Relevance
“…These prenatal piRNAs are involved not only in PTGS but also in TGS through de novo DNA methylation, because retrotransposons and at least one imprint control region are hypomethylated in Piwil2, Piwil4, and Pld6 (also known as mitoPLD) knockout prospermatogonia (Aravin et al 2007b;Carmell et al 2007;Kuramochi-Miyagawa et al 2008;Watanabe et al 2011). Thus, in the future, it might become possible to introduce epigenetic marks such as DNA methylation to specific genomic regions in germ cells, which could then be inherited by the progeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These prenatal piRNAs are involved not only in PTGS but also in TGS through de novo DNA methylation, because retrotransposons and at least one imprint control region are hypomethylated in Piwil2, Piwil4, and Pld6 (also known as mitoPLD) knockout prospermatogonia (Aravin et al 2007b;Carmell et al 2007;Kuramochi-Miyagawa et al 2008;Watanabe et al 2011). Thus, in the future, it might become possible to introduce epigenetic marks such as DNA methylation to specific genomic regions in germ cells, which could then be inherited by the progeny.…”
Section: Discussionmentioning
confidence: 99%
“…They are derived from retrotransposon-rich regions and loaded onto either of the two PIWI proteins, PIWIL2 (also known as MILI) or PIWIL4 (MIWI2) (Kuramochi-Miyagawa et al 2001;Kuramochi-Miyagawa et al 2004;Carmell et al 2007;Aravin et al 2008). Targeted disruptions of the two genes resulted in decreased DNA methylation in retrotransposon sequences and increased levels of their RNAs (Aravin et al 2007b(Aravin et al , 2008Kuramochi-Miyagawa et al 2008).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…For instance, spermatogenesis is arrested at the pachytene spermatocyte stage in Mili-knockout mice [203]. In Miwi2-knockout mice, spermatogenesis stops with meiotic arrest at the leptotene stage [204]. Germ cells in Miwi-deficient mice testis undergo meiosis without elongated spermatids or mature spermatozoa production [205].…”
Section: Mirnas In Spermmentioning
confidence: 99%
“…While MIWI2/Mili is essential for spermatogenesis and repression of transposons in the mouse male germ line, 30 Dnmt3a is an enzyme that catalyzes DNA methylation. 31 While DNA methylation facilitates the inhibitory effect of piRNAs on transposon expression and has important roles in embryonic development, 32 we found that Dnmt3a could methylate the miR-17 promoter, producing a feedforward loop.…”
Section: Discussionmentioning
confidence: 99%